Design and verification of an effective state‐of‐charge estimator for thermal energy storage. Issue 2 (16th March 2021) - Morales Sandoval, Daniel A.; De La Cruz Loredo, Iván; Bastida, Héctor; Badman, Jordan J. R.; Ugalde‐Loo, Carlos E.
Abstract: Thermal energy storage (TES) is widely used in district heating and cooling systems (DHCS) to act as a buffer between the supply and demand schedules. The adequate control of charging and discharging modes of TES may improve the overall performance of a DHCS and, to this end, an effective regulation of its state‐of‐charge (SoC) is required. However, the calculation of SoC depends on the availability and accuracy of temperature measurements. A model‐based observer for the calculation of the SoC of water‐based TES tanks is presented. A dynamic model of a one‐dimensional stratified water tank is adopted to develop the observer. Its effectiveness is assessed through 'model‐in‐the‐loop' cosimulations, with the observer and the feedback control system being implemented in MATLAB/Simulink and a high‐fidelity water tank component available in Apros being used as the plant model. Simulation results considering three different system configurations demonstrate that the model‐based observer accurately estimates the temperature distribution within the tank, leading to an effective SoC computation and control—even in the case of sensor failure or upon limited sensor availability.